Outlander - Gabaldon, Diana; Porter, Davina (Prince Frederick, Md. : Recorded Books, 1997)
In 1945, a former combat nurse, back from the war and on her honeymoon, touches a boulder in an ancient Scottish ruin and is instantly transported to a Scotland torn by war and raiding border clans in 1743.
Keywords: Time travel -- Fiction; Culloden, Battle of, 1746 -- Fiction; Jacobite Rebellion, 1745-1746 -- Fiction; Scotland -- Fiction -- History -- 18th century; Historical fiction; Fantastic fiction; War stories; Audiobooks